Method for producing DDR-type zeolite catalysts
Patent Information
- Application Number
- JP2022144246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-09-12
AI Technical Summary
【0009】 本発明によれば、エチレンの高収率化を達成できるDDR型ゼオライト触媒の製造方法を提供することができる。また、当該ゼオライトを低級オレフィン合成用の触媒として用いることができる。
Smart Images

Figure 0007943577000002 
Figure 0007943577000003 
Figure 0007943577000004
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing a DDR-type zeolite catalyst, and more particularly to a method for producing a DDR-type zeolite catalyst that can achieve a high yield of ethylene when used as a catalyst. [Background technology]
[0002] Traditionally, methods for producing lower olefins such as ethylene, propylene, and butene have included steam cracking of naphtha and fluid catalytic cracking of vacuum diesel fuel. In recent years, metathesis reactions using ethylene and 2-butene as raw materials, and the MTO (methanol to olefin) process using methanol and / or dimethyl ether as raw materials have become known.
[0003] For example, Non-Patent Documents 1 to 3 disclose that by using methanol as a raw material and a zeolite having a DDR-type structure (Sigma-1, ZSM-58 zeolite) as a catalyst, the by-product formation of hydrocarbon components of C5 or higher can be suppressed, and ethylene and propylene can be produced in high yield. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Catal.Sci.Technol.,6,2663-2678(2016) [Non-Patent Document 2] ACS Catal., 7, 4033-4046 (2017) [Non-Patent Document 3] ACS Catal., 10, 3009-3017 (2020) [Overview of the project] [Problems that the invention aims to solve]
[0005] Non-patent document 1 reports the ethylene yield for DDR-type zeolite with a particle size of approximately 2.5 μm, when the Si / Al2 ratio (calculated from NH3-TPD) is varied from 120 to 415. The results show that the higher the Si / Al2 ratio, the higher the ethylene yield, with the highest ethylene yield being around 43%. Furthermore, for a sample with a Si / Al2 ratio of 315, the ethylene yield when the particle size is varied is reported, and there is a tendency for the ethylene yield to be higher for samples with smaller particle sizes, with the highest ethylene yield being around 46%. Furthermore, Non-Patent Document 2 contains the results of a reaction evaluation of DDR-type zeolite with a Si / Al ratio of 50 and a particle size of approximately 500-1000 nm, showing that the maximum yield of ethylene was approximately 48%. Furthermore, Non-Patent Document 3 reports the results of a performance comparison of DDR-type zeolites with particle sizes of several μm and Si / Al ratios ranging from 22 to 172. The comparison is conducted in the range of methanol conversion rates of 45-55%, and the ethylene selectivity is maximized at Si / Al=22, showing a value of approximately 37%. However, sufficient research has not been conducted on the Si / Al ratio and particle size necessary to achieve high ethylene yield, and in particular, the optimal Si / Al ratio when the particle size is small remains unknown. For users who wish to selectively produce ethylene as a lower olefin, there is a need for zeolite catalysts that can achieve an ethylene yield exceeding 50%.
[0006] The present invention aims to solve the above problems and to provide a method for producing a DDR-type zeolite catalyst that can achieve a high yield of ethylene. [Means for solving the problem]
[0007] The inventors of the present invention conducted research to solve the above problems and discovered that by adding a surfactant to the synthetic raw material gel during the production of DDR-type zeolite, and by appropriately adjusting the molar ratio (Si / Al) of silicon (Si) and aluminum (Al) as constituent elements of the DDR-type zeolite, as well as the average primary particle size, it is possible to provide a DDR-type zeolite that can achieve a high yield of ethylene as a catalyst, thus completing the present invention.
[0008] The present invention includes the following gist. [1] A method for producing a DDR-type zeolite catalyst containing silicon (Si) and aluminum (Al) as constituent elements, wherein the molar ratio of silicon (Si) to aluminum (Al) (Si / Al) is 60 or more and 150 or less, and the average primary particle diameter is 1000 nm or less, A method for producing a DDR-type zeolite catalyst, characterized by adding a surfactant to a zeolite synthesis raw material gel. [2] A method for producing the DDR-type zeolite catalyst described in [1] above, wherein methyltropinium iodide is used as a structure-controlling agent. [3] A method for producing a DDR-type zeolite catalyst according to [1] or [2], wherein the ratio (A2 / A1) of the BET specific surface area (A2) calculated by the BET plot to the external surface area (A1) calculated by the t plot in nitrogen adsorption / desorption measurement is 20 or less. [4] A method for producing a DDR-type zeolite catalyst according to any one of [1] to [3] above, wherein the DDR-type zeolite catalyst is a catalyst for producing a lower olefin from a raw material containing methanol and / or dimethyl ether. [Effects of the Invention]
[0009] According to the present invention, a method for producing a DDR-type zeolite catalyst that can achieve a high yield of ethylene can be provided. Furthermore, this zeolite can be used as a catalyst for the synthesis of lower olefins. [Brief explanation of the drawing]
[0010] [Figure 1]This is a diagram showing the powder X-ray diffraction results of the DDR-type zeolite (H-form) according to Example 1. [Figure 2] This is a diagram showing the powder X-ray diffraction results of the DDR-type zeolites (as-made form) according to Comparative Examples 1 to 3. [Figure 3] These are scanning electron microscope (SEM) images of the DDR-type zeolites according to Example 1 and Comparative Examples 1 to 3. [Figure 4] This is a graph showing the trends in methanol conversion rate and selectivity in the production of lower olefins using the DDR-type zeolites according to Example 1 and Comparative Examples 1 to 3 as catalysts. [Mode for Carrying Out the Invention]
[0011] Hereinafter, the present invention will be described in detail. However, the description of the constituent elements set forth below is an example (representative example) of the embodiments of the present invention, and the present invention is not limited to these contents, and various modifications can be implemented within the scope of the gist of the present invention.
[0012] [DDR-type Zeolite] The DDR-type zeolite catalyst produced by the method of the present invention contains silicon (Si) and aluminum (Al) as constituent elements, has a molar ratio of silicon (Si) to aluminum (Al) (Si / Al) of 60 or more and 150 or less, and has an average primary particle diameter of 1000 nm or less.
[0013] DDR-type zeolite is a zeolite having a two-dimensional pore structure with a shape in which two 8-membered ring structures intersect as its structural unit. According to the IZA database, the pore diameter is 3.6 × 4.4 Å. Compared with CHA-type zeolite (3.8 × 3.8 Å) represented by SAPO-34 which has been industrialized as an MTO catalyst, it has a narrowed pore structure, and therefore it is presumed that the by-production of hydrocarbon components of C5 or higher can be suppressed.
[0014] As described above, the DDR-type zeolite produced by the method of the present invention contains silicon (Si) and aluminum (Al) as constituent elements, has a molar ratio of silicon (Si) to aluminum (Al) (Si / Al) of 60 to 150, and has an average primary particle diameter of 1000 nm or less.
[0015] By having a molar ratio of silicon (Si) to aluminum (Al) (Si / Al) and an average primary particle size within the above range, ethylene can be obtained in high yield when producing lower olefins. Specifically, the molar ratio of silicon (Si) to aluminum (Al) (Si / Al) is preferably 70 or higher, more preferably 75 or higher, and even more preferably 80 or higher. Having a Si / Al ratio within this range suppresses the by-product formation of paraffins such as methane. Furthermore, the Si / Al ratio is preferably 140 or lower, more preferably 130 or lower. Having a Si / Al ratio within this range makes the cracking reaction that produces ethylene more likely to occur.
[0016] In addition, the average primary particle diameter must be 1000 nm or less, preferably 900 nm or less, more preferably 800 nm or less, and even more preferably 700 nm or less. Having the average primary particle diameter within this range suppresses the formation of paraffin by-products such as methane. The lower limit is not particularly limited, but is usually 20 nm or more, preferably 40 nm or more, and particularly preferably 60 nm or more.
[0017] Both "primary particle diameter" and "average primary particle diameter" can be calculated using a scanning electron microscope (SEM). Here, "primary particles" refer to the smallest particles in which no grain boundaries can be identified. In this invention, an SEM image of the zeolite catalyst is obtained, and the smallest particles in the portion corresponding to the zeolite included in the SEM image in which no grain boundaries can be identified are determined to be "primary particles." In this invention, primary particles do not necessarily exist as individual particles, and secondary particles may be formed by aggregation or the like. Even if secondary particles are formed, primary particles on the surface of the secondary particles can be identified in the SEM image. Note that DDR-type zeolites may show crack-like features on their surface, but these are not included in the definition of primary particles. The "average primary particle diameter" is measured as follows: 50 primary particles are randomly selected from the SEM image of the zeolite catalyst. For each of these 50 selected primary particles, the major axis (the length of the longest straight line connecting one end of the primary particle to the other) is measured. The arithmetic mean of these 50 major axes is defined as the "average primary particle diameter." However, if the zeolite catalyst contains fewer than 50 primary particles, the major axis of all primary particles in the zeolite catalyst is measured, and the average of these measurements is defined as the "average primary particle diameter."
[0018] Setting the average primary particle size within a specific range can be achieved, for example, by using DDR-type zeolite with a small particle size as a seed crystal, or by adding a surfactant to the zeolite synthesis raw material gel during the manufacturing process of DDR-type zeolite.
[0019] Other elements besides silicon (Si) and aluminum (Al) that may be included as constituent elements in the DDR-type zeolite produced by the method of the present invention are not particularly limited, but examples include one or more selected from boron (B), titanium (Ti), vanadium (V), iron (Fe), zinc (Zn), gallium (Ga), germanium (Ge), zirconium (Zr), and tin (Sn).
[0020] Specifically, preferred examples include crystalline aluminosilicates containing Si and Al as constituent elements, as well as crystalline galloaluminosilicates containing Ga. These zeolites exhibit excellent catalytic activity because the Al and Ga within the zeolite framework act as acid sites, which are active sites in catalytic reactions.
[0021] In the case of crystalline galloaluminosilicate containing Ga in addition to Si and Al as constituent elements, the Ga content ratio is not particularly limited, but it is preferable that the Si / Ga molar ratio is 50 or more, particularly 100 or more, especially 200 or more, and 4000 or less, particularly 2000 or less, and especially 1000 or less. Furthermore, it is preferable that the Ga / Al molar ratio is 0.1 or more, particularly 0.2 or more, especially 0.4 or more, and 8 or less, particularly 4 or less, and especially 2 or less. By using the above Si / Ga molar ratio and Ga / Al molar ratio, it is possible to obtain a zeolite catalyst that has sufficient catalytic activity and an extremely excellent catalyst lifetime, which is preferable.
[0022] It should be noted that the Si, Al, Ga, etc. content of the DDR-type zeolite produced by the method of the present invention is the value measured for the produced DDR-type zeolite by inductively coupled plasma atomic emission spectroscopy (ICP-AES), etc., and does not represent the ratio of the raw materials used.
[0023] The ion exchange sites of the DDR-type zeolite produced by the method of the present invention are not particularly limited and may be H-type or exchanged with metal ions. Specifically, metal ions include alkali metal ions, alkaline earth metal ions, cerium, tungsten, manganese, iron, etc.
[0024] [Ratio of BET specific surface area (A2) to external surface area (A1)] The outer surface area (A1) of the DDR-type zeolite produced by the method of the present invention is typically 5 m². 2 / g or more, preferably 10m 2 / g or more, comfortable 15m 2 / g or more, more preferably 20m 2 / g or more, still more preferably 25 m 2 / g or more, particularly preferably 30 m 2 / g or more, and usually 500 m 2 / g or less, preferably 300 m 2 / g or less, more preferably 200 m 2 / g or less. The BET specific surface area (A2) of the DDR-type zeolite produced by the method of the present invention is usually 150 m 2 / g or more, preferably 200 m 2 / g or more, more preferably 250 m 2 / g or more, further preferably 300 m 2 / g or more, particularly preferably 350 m 2 / g or more, and usually 1000 m 2 / g or less, preferably 800 m 2 / g or less, more preferably 700 m 2 / g or less. The ratio of the BET specific surface area (A2) to the external surface area (A1) (A2 / A1) of the DDR-type zeolite produced by the method of the present invention is preferably 20 or less. When A2 / A1 is 20 or less, diffusion of the reaction product out of the pores is improved, and coking is considered to be suppressed. From the above viewpoint, A2 / A1 is more preferably 18 or less, further preferably 16 or less, still more preferably 14 or less, and particularly preferably 12 or less. On the other hand, the lower limit is not particularly limited, but is usually 2 or more. The micropore volume (A3) of the DDR-type zeolite produced by the method of the present invention is not particularly limited, and is usually 0.05 mL / g or more, preferably 0.075 mL / g or more, more preferably 0.10 mL / g or more, and usually 3 mL / g or less, preferably 2 mL / g or less. The external surface area (A1), BET specific surface area (A2), and micropore volume (A3) can be calculated from nitrogen adsorption / desorption measurements, for example, using a Belsorp-miniII manufactured by Microtrac-Bell. Data analysis can then be performed using BELMaster, analysis software also manufactured by Microtrac-Bell. Here, the BET specific surface area (A2) can be calculated by plotting BET data for relative pressure (P / P0) values between 0.002 and 0.06. The external surface area (A1) and micropore volume (A3) can be calculated by plotting t-plot data for relative pressure (P / P0) values between 0.20 and 0.42. The Harkins-Jura isotherm is used as the standard isotherm.
[0025] [Method for producing DDR-type zeolite catalysts] The method for producing the DDR-type zeolite catalyst of the present invention will be described below.
[0026] DDR-type zeolites can generally be prepared by hydrothermal synthesis. For example, an alkali source and an organic structure-regulating agent, preferably 1-adamantylamine, methyltropinium iodide, or quinuclidinium hydroxide, are added to water and stirred. Further, an aluminum source, gallium source, boron source, or silica source is added to form a homogeneous gel. The resulting raw material gel is then held at 100-220°C in a pressurized heating vessel such as an autoclave to crystallize. Among the above organic structure-regulating agents, methyltropinium iodide is particularly preferred because it easily yields DDR-type zeolites with a small average primary particle size and a small (A2 / A1) value. Furthermore, seed crystals may be added during crystallization as needed, and adding seed crystals is preferable because it facilitates the crystallization of DDR-type zeolite. It is preferable to use DDR-type zeolite as the seed crystal. It is preferable to use zeolite that has undergone pulverization as the seed crystal, as using pulverized seed crystals makes it easier to obtain DDR-type zeolite with small particle sizes.
[0027] <Surfactants> The manufacturing method of the present invention is characterized by the addition of a surfactant to the raw material gel during crystallization. By adding a surfactant, the zeolite is made into microparticles, making it easier to adjust the average primary particle size and the (A2 / A1) value to a desired range. As surfactants, cationic surfactants, anionic surfactants, nonionic surfactants, amphoteric surfactants, etc., can be used individually or in combination. Cationic surfactants that act as appropriate crystal growth inhibitors are preferred as surfactants, and examples include hexadecyltrimethylammonium bromide (cetyltrimethylammonium bromide (CTAB)), hexadecyltrimethylammonium chloride (cetyltrimethylammonium chloride), and hexadecyltrimethylammonium hydroxide (cetyltrimethylammonium hydroxide).
[0028] The amount of surfactant added to the raw material gel is not particularly limited, but the molar ratio of the raw material gel to Si is preferably 0.001 or more, more preferably 0.002 or more, particularly preferably 0.005 or more, also preferably 0.05 or less, more preferably 0.03 or less, and particularly preferably 0.015 or less.
[0029] After the crystallization of the raw material gel, the crystallized raw material gel is filtered and washed, the solid components are dried at 100-200°C, and then calcined at 400-900°C to obtain zeolite powder.
[0030] As silica sources used in the preparation of the raw material gel, one or more types of silicates such as fumed silica, silica sol, silica gel, silicon dioxide, and water glass, as well as silicon alkoxides such as tetraethoxyorthosilicate and tetramethoxysilane, and silicon halides can be used. As an aluminum source, one or more of the following can be used: aluminum sulfate, aluminum nitrate, boehmite pseudo, aluminum alkoxide, aluminum hydroxide, alumina sol, sodium aluminate, etc. One or more of the following can be used as the gallium source: gallium nitrate, gallium sulfate, gallium phosphate, gallium chloride, gallium bromide, gallium hydroxide, etc. One or more boron sources can be used, such as boric acid, sodium borate, or boron oxide.
[0031] There are no particular restrictions on the molar ratio (Si / Al) of silicon (Si) to aluminum (Al) in the DDR-type zeolite used as seed crystal, but it is preferably in the range of 25 to 10000. Furthermore, it is preferable to use about 1 to 20% by mass of the seed crystal relative to the silica source added.
[0032] DDR-type zeolites allow for adjustment of the metal content by controlling the amounts of constituent elements (Si, Al, Ga, B, etc.) during synthesis. Alternatively, zeolites with adjusted content can be used by removing some of the constituent elements through methods such as steaming or acid treatment.
[0033] [catalyst] The DDR-type zeolite produced by the method of the present invention can be used as a catalyst. In particular, the DDR-type zeolite produced by the method of the present invention is useful as a catalyst used in reactions that produce lower olefins. On the other hand, the applications of the DDR-type zeolite catalyst produced by the method of the present invention are not limited to catalysts for the production of lower olefins, but can be used as catalysts for the production of various hydrocarbons. For example, it can be suitably used in the production of p-xylene, ethylbenzene, cumene, aromatization of light hydrocarbons, hydrocracking, dewaxing, and isomerization of alkanes. In this specification, lower olefins refer to ethylene, propylene, and butene. In other words, olefins having 2 to 4 carbon atoms.
[0034] The DDR-type zeolite produced by the method of the present invention may be used as a catalyst in the reaction as is, or it may be used as a mixture with other substances that are inert to the reaction, such as alkaline earth metals or silicon-containing compounds. Alternatively, it may be granulated or molded using a binder before being used in the reaction. Examples of substances that are inert to the reaction or binders include alumina or alumina sol, silica, silica gel, silicates, quartz, and mixtures thereof. Among these, silica is preferred because it is expected to have excellent strength and catalytic performance as an industrial catalyst. Mixing with these substances is also effective in reducing the overall cost of the catalyst, increasing the density of the catalyst, and increasing the catalytic strength.
[0035] [Method for producing lower olefins] In a method for producing lower olefins using a catalyst containing DDR-type zeolite produced by the method of the present invention, methanol and dimethyl ether are examples of raw materials, but are not limited thereto, and can be appropriately selected depending on the type of olefin to be produced.
[0036] The following describes a method for producing lower olefins using the above catalyst, with an example where the raw materials are methanol and / or dimethyl ether.
[0037] The present invention provides a method for producing lower olefins, comprising the step of contacting a catalyst containing the above-mentioned DDR-type zeolite with a raw material containing methanol and / or dimethyl ether.
[0038] The origin of methanol and dimethyl ether used as raw materials is not particularly limited. Examples include those obtained by hydrogenation reactions of hydrogen / CO mixed gases derived from coal, natural gas, and by-products in the steel industry; those obtained by reforming reactions of plant-derived alcohols; those obtained by fermentation; those obtained from organic materials such as recycled plastics and municipal waste; and those obtained by methanol synthesis reactions using carbon dioxide as a raw material. In this case, methanol and dimethyl ether may be used as is, or purified methanol may be used, as they may contain any mixture of other compounds resulting from each manufacturing method. The reaction materials may consist of methanol alone, dimethyl ether alone, or a mixture of both. When methanol and dimethyl ether are used as a mixture, there are no restrictions on the mixing ratio.
[0039] The reaction mode in this embodiment is not particularly limited as long as the methanol and / or dimethyl ether feedstocks are in the gas phase in the reaction zone, and known gas-phase reaction processes using fluidized bed reactors, moving bed reactors, or fixed bed reactors can be applied. Using a fluidized bed reactor makes it possible to operate even with catalysts that have a short single-pass life. Furthermore, the process can be carried out in batch, semi-continuous, or continuous form, but continuous is preferred, and this method may involve using a single reactor or using multiple reactors arranged in series or parallel.
[0040] Furthermore, when filling the fixed-bed reactor with the aforementioned catalyst, in order to minimize the temperature distribution of the catalyst layer, granular material that is inert to the reaction, such as quartz sand, alumina, silica, or silica-alumina, may be mixed with the catalyst before filling. In this case, there are no particular restrictions on the amount of granular material that is inert to the reaction, such as quartz sand, used. However, it is preferable that the particle size of this granular material is similar to that of the catalyst, in terms of uniform mixing with the catalyst. Furthermore, the reaction substrate (reaction raw material) may be supplied to the reactor in divided portions in order to disperse the heat generated by the reaction.
[0041] There are no particular restrictions on the total concentration (substrate concentration) of methanol and dimethyl ether in the total feed components supplied to the reactor, but the sum of methanol and dimethyl ether is preferably 90 mol% or less of the total feed components. More preferably it is 10 mol% to 70 mol%. The above range is preferable in terms of reaction rate and lower olefin yield.
[0042] In addition to methanol and / or dimethyl ether, the reactor may contain other gases that are inert to the reaction (hereinafter also referred to as "diluents"), such as helium, argon, nitrogen, carbon monoxide, carbon dioxide, hydrogen, water, paraffins, hydrocarbons such as methane, aromatic compounds, and mixtures thereof. Among these, the presence of water (water vapor) is preferable because it allows for good separation. As such a diluent, the impurities contained in the reaction raw materials may be used as is, or a separately prepared diluent may be mixed with the reaction raw materials before use. Furthermore, the diluent may be mixed with the reaction raw materials before being placed in the reactor, or it may be supplied to the reactor separately from the reaction raw materials.
[0043] The lower limit of the reaction temperature is usually about 200°C or higher, preferably 250°C or higher, more preferably 300°C or higher, and particularly preferably 400°C or higher. The upper limit of the reaction temperature is usually 750°C or lower, preferably 700°C or lower, and more preferably 600°C or lower. If the reaction temperature is too low, the reaction rate is slow, a large amount of unreacted raw materials tend to remain, and the yield of lower olefins also decreases. On the other hand, if the reaction temperature is too high, it is difficult to obtain stable catalyst activity, and the yield of lower olefins decreases significantly. Here, the reaction temperature refers to the temperature at the outlet of the catalyst layer.
[0044] The upper limit of the reaction pressure is usually preferably 5 MPa (absolute pressure, the same applies hereinafter) or less, more preferably 2 MPa or less, even more preferably 1 MPa or less, even more preferably 0.7 MPa or less, and particularly preferably 0.4 MPa or less. The lower limit of the reaction pressure is not particularly limited, but is usually 0.1 kPa or more, preferably 7 kPa or more, and more preferably 50 kPa or more. If the reaction pressure is below the above upper limit, the amount of undesirable by-products such as paraffins and aromatic compounds is suppressed, and the yield of lower olefins increases. On the other hand, if the reaction pressure is above the above lower limit, a sufficient reaction rate can be obtained.
[0045] The weight space velocity of the reaction raw materials is 0.1hr -1 Preferably, it should be 0.5hr -1 The above is more preferable. On the other hand, the gravitational space velocity is 10hr -1 The following is preferable: 5hr -1 The following is more preferable: When the gravimetric space velocity is within this range, the yield of lower olefins is improved.
[0046] The reactor outlet gas (reactor effluent) is a mixed gas containing the reaction product, a lower olefin, a by-product, and a diluent. The concentration of the lower olefin in the mixed gas is typically 5 to 95% by mass. Depending on the reaction conditions, the reaction product may contain unreacted methanol and / or dimethyl ether as raw materials. However, it is preferable to carry out the reaction under conditions where the conversion rate of methanol and / or dimethyl ether is high. This facilitates the separation of the reaction product from the unreacted raw materials. In particular, it is preferable to carry out the reaction under conditions where the conversion rate of methanol and / or dimethyl ether is 100%, as this eliminates the need to separate the reaction product from the unreacted raw materials. By-products include olefins with 5 or more carbon atoms, paraffins, aromatic compounds, and water.
[0047] The mixed gas, which is the reaction product (lower olefin), unreacted raw materials, by-products, and diluents, is introduced into a known separation and purification facility and treated by recovery, purification, recycling, or discharge according to each component. [Examples]
[0048] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to the following examples.
[0049] [Example 1] 0.183 g of sodium hydroxide, 0.0237 g of aluminum sulfate, and 10.00 g of water were mixed, and 0.982 g of methyltropinium iodide, an organic structure-determining agent, was added and stirred. Then, 0.833 g of CAB-O-SIL M7D (manufactured by Cabot Corporation) was added as a silica source and stirred thoroughly. Furthermore, 0.0506 g of cetyltrimethylammonium bromide (CTAB), a surfactant, was added and stirred, and 0.050 g of DDR-type zeolite was added as a seed crystal and stirred to prepare the raw material gel.
[0050] The obtained raw material gel was placed in an autoclave and heated at 160°C, 40 rpm for 2 days. After filtering and washing the product with water, it was dried at 100°C to obtain an as-made type white powder. X-ray diffraction (XRD) patterns of the product confirmed that the obtained product was a DDR type zeolite. Note that "as-made type" means the state after drying and before calcination of the organic structure-controlling agent.
[0051] The obtained zeolite powder was calcined at 600°C for 6 hours in an air atmosphere to obtain sodium-type zeolite powder. The obtained powder was subjected to ion exchange in a 2.5N ammonium nitrate aqueous solution at 80°C for 3 hours, and then filtered and dried. The dried powder was again subjected to ion exchange in a 2.5N ammonium nitrate aqueous solution at 80°C for 3 hours, and then filtered and dried to obtain ammonium-type zeolite powder. This was then calcined at 600°C for 6 hours in an air atmosphere to obtain the proton-type zeolite of Example 1.
[0052] [Comparative Example 1] 3.65 g of 1 M sodium hydroxide aqueous solution, 0.30 g of 1-adamantylamine, and 9.61 g of water were mixed, and 0.125 g of aluminum sulfate was added and stirred. Then, 3.96 g of Cataloid SI-30 (manufactured by JGC Catalysts & Chemicals Co., Ltd.) was added as a silica source and stirred thoroughly. Furthermore, 0.072 g of pulverized DDR-type zeolite was added as a seed crystal and stirred to prepare the raw material gel.
[0053] The obtained raw material gel was placed in an autoclave and heated at 160°C for 1 day. The product was filtered, washed with water, and dried at 100°C to obtain an as-made type white powder. X-ray diffraction (XRD) patterns of the product confirmed that the obtained product was a DDR type zeolite.
[0054] The obtained zeolite powder was calcined at 600°C for 6 hours in an air atmosphere to obtain sodium-type zeolite powder. The obtained powder was subjected to ion exchange in a 1N ammonium nitrate aqueous solution at 80°C for 1 hour, and then filtered. The filtered powder was again subjected to ion exchange in a 1N ammonium nitrate aqueous solution at 80°C for 1 hour, and then filtered and dried to obtain ammonium-type zeolite powder. Subsequently, it was calcined at 500°C for 6 hours in an air atmosphere to obtain the proton-type zeolite of Comparative Example 1.
[0055] [Comparative Example 2] 3.62 g of 1M aqueous sodium hydroxide solution, 0.30 g of 1-adamantylamine and 9.61 g of water were mixed, 0.015 g of aluminum sulfate was added thereto and stirred, then 3.95 g of Cataloid SI-30 (manufactured by JGC Catalysts and Chemicals Ltd.) was added as a silica source, followed by sufficient stirring. Further, 0.072 g of pulverized DDR-type zeolite was added as seed crystals, and the mixture was stirred to prepare a raw material gel. The obtained raw material gel was heated and post-treated in the same manner as in Comparative Example 1 to obtain the proton-type zeolite powder of Comparative Example 2.
[0056] [Comparative Example 3] 8.37 g of 1M aqueous sodium hydroxide solution, 0.61 g of 1-adamantylamine and 23.73 g of water were mixed, 0.124 g of aluminum sulfate was added thereto and stirred, then 2.40 g of Aerosil 200 (manufactured by Nippon Aerosil Co., Ltd.) was added as a silica source, followed by sufficient stirring to prepare a raw material gel. The obtained raw material gel was heated and post-treated in the same manner as in Comparative Example 1, except that it was heated at 160°C for 5 days, to obtain the proton-type zeolite powder of Comparative Example 3.
[0057] The synthesis conditions for Example 1 and Comparative Examples 1 to 3 are summarized in Table 1.
[0058] [Evaluation of Zeolite] The following evaluations were performed on the zeolites of Example 1 and Comparative Examples 1 to 3.
[0059] <X-ray Diffraction Measurement> X-ray diffraction (XRD) measurement of the synthesized zeolite was performed using "D2 PHASER" manufactured by BRUKER. The XRD patterns of the zeolite according to Example 1 and the zeolites according to Comparative Examples 1 to 3 are shown in Figure 1 and Figure 2, respectively. From Figure 1 and Figure 2, it was confirmed that all the zeolites according to Example 1 and Comparative Examples 1 to 3 have a DDR-type structure.
[0060] <Elemental Analysis> Elemental analysis was performed by inductively coupled plasma atomic emission spectroscopy (ICP-AES). For the zeolite in Example 1, a Shimadzu ICPE-9000 was used. For the zeolites in Comparative Examples 1-3, a Thermo Fisher Scientific iCAP7600Duo was used. Table 1 shows the Si / Al molar ratios of the synthesized zeolites.
[0061] <Scanning Electron Microscope> Scanning electron microscope (SEM) observations for Example 1 were performed using a JEOL Ltd. "JSM-6010LV". Scanning electron microscope (SEM) measurements for Comparative Examples 1 and 2 were performed using a Zeiss "ULTRA55". SEM measurements for Comparative Example 3 were performed using a Hitachi High-Technologies Corporation "S-4800". Figure 3 shows SEM images of the zeolite catalysts for Example 1 and Comparative Examples 1-3. Figure 3 is a 10,000x magnification image. Fifty primary particles were randomly selected from the obtained SEM images, and the major axis of each particle was measured to determine the particle diameter. For Comparative Example 3, since the particle diameter was large, the particle diameter was measured using a 4,000x magnification image. The arithmetic mean of the obtained particle diameters was used as the average primary particle diameter. The results are shown in Table 1.
[0062] <Nitrogen adsorption / desorption measurement> Nitrogen adsorption and desorption measurements of the synthesized zeolite were performed using the "Belsorp-miniII" manufactured by Microtrac-Bell. For the measurements, the zeolite was heated and dried under vacuum at 400°C for 2 hours, and then nitrogen adsorption and desorption measurements were performed at liquid nitrogen temperature. Data analysis was performed using BELMaster, analysis software manufactured by Microtrac-Bell. The BET specific surface area (A2) was calculated by plotting the BET data for relative pressures (P / P0) of 0.002 to 0.06. The external surface area (A1) and micropore volume (A3) were calculated by plotting the data for relative pressures (P / P0) of 0.20 to 0.42. The Harkins-Jura isotherm was used as the standard isotherm.
[0063] <Manufacturing of lower olefins> Lower olefins were produced using the zeolites obtained in Example 1 and Comparative Examples 1-3. A fixed-bed flow reactor was used for the reaction, and 100 mg of pre-mixed proton-type zeolite powder and 400 mg of quartz sand were packed into a 6 mm inner diameter quartz reaction tube. A mixed gas of 50 mol% methanol and 50 mol% nitrogen was introduced at a methanol weight space velocity of 1 hr. -1 The mixture was supplied to the reactor as described above, and the reaction was carried out at 450°C and 0.1 MPa (absolute pressure). The product was analyzed by gas chromatography every hour from the start of the reaction. Figure 4 shows a graph illustrating the changes in methanol conversion rate and selectivity. Table 1 shows the methanol conversion rate (%), ethylene yield (C-mol%), propylene yield (C-mol%), butene yield (C-mol%), and catalyst lifetime (hr) after 3 hours from the start of the reaction. Catalyst lifetime was defined as the time during which the methanol conversion rate remained above 90%. In addition, the average values for methanol conversion rate (%), ethylene yield (C-mol%), propylene yield (C-mol%), and butene yield (C-mol%) from 2 hours to 4 hours after the start of the reaction are also shown.
[0064] [Table 1]
[0065] As shown in Table 1, the DDR-type zeolite produced by the manufacturing method described in Example 1, which contains the surfactant CTAB as a raw material for zeolite synthesis, exhibits a high ethylene yield.
Claims
1. A method for producing a DDR-type zeolite catalyst containing silicon (Si) and aluminum (Al) as constituent elements, wherein the molar ratio of silicon (Si) to aluminum (Al) (Si / Al) is 60 or more and 150 or less, and the average primary particle diameter is 1000 nm or less, The DDR-type zeolite catalyst is a catalyst for producing ethylene from a raw material containing methanol and / or dimethyl ether. A method for producing a DDR-type zeolite catalyst, characterized by adding a cationic surfactant to a zeolite synthesis raw material gel.
2. The method for producing a DDR-type zeolite catalyst according to Claim 1, wherein the amount of cationic surfactant added to the raw material gel is 0.001 or more and 0.05 or less as a molar ratio to Si of the raw material gel.
3. A method for producing a DDR-type zeolite catalyst according to claim 1, wherein methyltropinium iodide is used as a structure-controlling agent.
4. The method for producing a DDR-type zeolite catalyst according to Claim 1, wherein the cationic surfactant is at least one selected from hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and hexadecyltrimethylammonium hydroxide.
5. The method for producing a DDR-type zeolite catalyst according to claim 1, wherein the ratio (A2 / A1) of the BET specific surface area (A2) calculated by the BET plot to the external surface area (A1) calculated by the t plot in nitrogen adsorption / desorption measurement is 20 or less.
Citation Information
Patent Citations
Crystalline silicate and synthesization therefor
JP1987027321A
SYNTHETIC METHOD OF BETA(beta)-ZEOLITE
JP2008239450A
Catalyst for producing olefin from methanol
JP2009255014A
Synthesis of zsm-58 crystals with improved diffusivity in gas separation applications
JP2017502906A
Con type zeolite, method for producing con type zeolite, and method for producing lower olefin
JP2021147310A